2003
DOI: 10.1002/anie.200352194
|View full text |Cite
|
Sign up to set email alerts
|

A Thiazyl‐Based Organic Ferromagnet

Abstract: In 1928 Heisenberg proposed [1] that bulk ferromagnetic order would only ever be achieved in systems containing heavy atoms, that is, metals, their oxides, and related derivatives. Indeed it was not until 1991 that the first organic ferromagnet was reported; the b-polymorph of the para-nitrophenyl nitronyl nitroxide radical (p-NPNN, 1; Scheme 1) was shown to order below 0.6 K. [2] Since then a number of other purely organic radicals have been found to undergo bulk ferromagnetic order, although the majority ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
94
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 133 publications
(98 citation statements)
references
References 15 publications
4
94
0
Order By: Relevance
“…Previous EPR studies [12,7] on 1 -3 indicate that the unpaired spin density distribution in these systems is almost invariant of the substituent on the perfluoroaryl group. In addition there is excellent agreement between the spin densities calculated from EPR and ab initio calculations.…”
Section: Theoretical Studies Onmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous EPR studies [12,7] on 1 -3 indicate that the unpaired spin density distribution in these systems is almost invariant of the substituent on the perfluoroaryl group. In addition there is excellent agreement between the spin densities calculated from EPR and ab initio calculations.…”
Section: Theoretical Studies Onmentioning
confidence: 92%
“…Many of these radicals have been isolated in the solid state. Whilst the majority form diamagnetic closed-shell dimers via a π*-π* dimerisation process, [ 4 ] a small number of perfluorophenyl derivatives 1-3 have recently been found which retain their paramagnetism in the solid state [5,6,7]. Radical 1 is polymorphic; the α-phase exhibits a maximum in χ around 8 K indicative of antiferromagnetic ordering, [5a] whilst the β-phase undergoes a phase transition to a canted antiferromagnetic phase at 36 K [5b].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preliminary x-ray and magnetic studies of 2 have been reported in a previous communication. 11 Large single crystals for the work described here were prepared by annealing a small sample ͑approximately 60 mg͒ in a sealed tube under N 2 for 3-4 hours at 100°C. While there was evidence for some decomposition ͑formation of an intractable brown oil on the surface of the glass͒, a small number of large single crystals were also formed with upper dimensions in the region 1 ϫ 1 ϫ 1 mm 3 .…”
Section: A Synthesismentioning
confidence: 99%
“…In this paper, we implement polarized neutron diffraction, electron paramagnetic resonance ͑EPR͒, and electron-nuclear double resonance ͑ENDOR͒ spectroscopies to experimentally probe the spin density distribution in p-O 2 NC 6 F 4 CNSSN, which some of us have previously reported to exhibit ferromagnetism below 1.3 K. 11 In addition these experimental studies are supported by ab initio densityfunctional theory ͑DFT͒ calculations ͑Preliminary reports of selected aspects of this study have been presented elsewhere 9,12 ͒. This combination of experimental and theoretical methods provides a self-consistent unified view of the spin density distribution within the dithiadiazolyl ring.…”
Section: Introductionmentioning
confidence: 99%